2018
DOI: 10.4314/ijbcs.v11i5.1
|View full text |Cite
|
Sign up to set email alerts
|

Atropine exposure in adolescence predispose to adult memory loss in Wistar rats

Abstract: Some of the brain malfunctions in adulthoods have been linked to the developmental process in their childhood, especially in most adolescent who have been exposed to one form of drug abuse or another. This study investigated the effect of atropine exposure at adolescence on the memory and histology of the frontal cortex of Wistar rats and its effects on adult memory. 20 male adolescent Wistar rats were used for the study. The rats were divided into two groups of 10 rats each. The first group were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This indicates the memory effect of NMDAR electrical activity. Memory decline has been attributed to datura use [ 51 ], although some authors attributed this effect to the anticholinergic properties of the plant [ [52] , [53] , [54] , [55] , [56] ]. Our results have shown that tropane alkaloids are not only phytochemical in D. metel that induce memory deficit and that datumetine can also play a major role.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the memory effect of NMDAR electrical activity. Memory decline has been attributed to datura use [ 51 ], although some authors attributed this effect to the anticholinergic properties of the plant [ [52] , [53] , [54] , [55] , [56] ]. Our results have shown that tropane alkaloids are not only phytochemical in D. metel that induce memory deficit and that datumetine can also play a major role.…”
Section: Discussionmentioning
confidence: 99%
“…However, phytochemical analysis of DM has revealed the presence of other active compounds such as alkaloids, tannins, steroids, saponins, scopolamine, atropine, flavonoids, phenols, and glycosides. Electrolytes such as calcium, magnesium, and iron are found in the seeds, roots, and leaves [ 4 , 8 , 10 , 80 ], while other chemical components of this plant include ( +)-pinoresinol-O-β-D-diglucopyranoside, ( +)-pinoresinol-O-β-D-glucopyranoside, p-tyrosol, trans-N-p-coumaroyltyramine, cis-N-p-coumaroyltyramine, 4-hydroxy-N-(4-hydroxyphenethyl) benzamide, phenylethyl beta -D-glucopyranoside, kaempferol-3-O-β-D-glucopyranosyl-(1–2)-β-D-galactopyranosyl-7-O-L-Rhamnopyranoside, and kaempferol-3-L-Rhamnopyranoside [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting mixture was filtered with Whitman filter paper (No.1) and concentrated to dryness using a vacuum rotary evaporator at 40 0 C. A yield of 75 g of dark green hygroscopic paste-like residue was obtained, stored in universal bottles and refrigerated at 4 0 C for subsequent use. The dosage of DM administration was based on results obtained from our pilot and previous studies, which reported LD50 of DM as 328.5 mg/kg/b.wt [ 10 , 82 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation